Murder on the middle passage : the trial of Captain Kimber - Rogers, Nicholas (The Boydell Press, 2020)
On 2 April 1792, John Kimber, captain of the Recovery, a slave ship from Bristol, was denounced in the House of Commons by William Wilberforce for flogging a fifteen-year old female slave to death. The story, caricatured in a contemporary Isaac Cruikshank print, raced across newspapers in Britain and Ireland and was even reported in America. Soon after, Kimber was indicted for murder.